Control tests of shotcrete with fibers in the tunnel of metro line 12 from CDMX - Aire, Carlos; Aguilar, Lilia (Revista ALCONPAT, 2021)
This paper three tests are evaluated to characterize the behavior of Shotcrete with metallic fibers in the primary lining of the tunnel on metro line 12 from CDMX. Three square panels (UNE 14488-5), three round panels (ASTM C1550) and four cylinders for Barcelona test (UNE 83515) were made. All can be used as quality control methods for Fiber Reinforced Concrete (FRC) in underground constructions, however, greater variability was found in the results of circular panels, in addition to being the specimens with the greatest complexity for their elaboration and test, therefore, the application of the Barcelona test is recommended for quality control on site because it is easier to prepare, handle and perform sampling and testing.